The interdisciplinarity of geography and geoprocessing in the mapping of Covid 19 cases in the municipality of João Monlevade- Minas Gerais (Research, Society and Development, 2020)
Interdisciplinarity enables the exchange between numerous areas of scientific knowledge. In its scenarios it is evident: interdependence between themes, relevance of perspective, interaction, dialogue and reciprocity between multiple knowledge. Geoprocessing harmonizes with the interdisciplinary scenarios, as it covers: Informatics, Geography, Cartography, Mathematics, logic and other educational themes. The aim of this study is to present the result of an epidemiological mapping project that used geoprocessing and information technology to produce spatial analysis. This is the project to map the Covid 19 epidemic in the geographic space of the municipality of João Monlevade, Minas Gerais, carried out by a student in the Environmental Engineering course at the State University of Minas Gerais - UEMG. For this, data on confirmed cases and deaths were collected at the city's Municipal Health Department. Mappings of the spatial spread of the disease were made using the QGIS 3.1 software, in which possible structural causes that contributed to the spread of the disease were verified. The results obtained by the mapping made it possible to identify human mobility structures concentrated in some municipalities in the Middle Piracicaba region. It is concluded that the mapping of COVID-19 data, made it possible to analyze demographic factors, taking into account that geotechnologies and geoprocessing techniques are shown as essential tools for analyzing the territory and understanding possible causes of the spread of the disease.